CULTURAL CONTEXT AS THE BASIS OF ART AND PEDAGOGICAL DIALOGUE - Ashikhmina, Nataliia; Korchevna, Svitlana (Revista Inclusiones, 2020)
In article a thesis was proposed that Art and pedagogical dialogue is the co-creation by “Ego” of many faces, the meeting of subjects with diverse style of thinking and cultural horizons of surrounding art and educational reality that extends considerably the borders of the individual cultural essence view and enables to comprehend them more deeply. Such kind of comprehension can be efficient if based on culturological approach that transmits cultural context. The implementation of this approach will enable to regard art education and development as the process of dialogical environment creation for the search and understanding the cultural senses via cognition of artistic image invariance.